The role of the public bureaucracy in policy implementation in five Asean countries - Quah, Jon S. T. (Integration through law: the role of law and the rule of law in Asean integration, 2015)
"This pioneering book addresses an important gap in the literature by comparing the role of the public bureaucracies in policy implementation in Indonesia, Malaysia, the Philippines, Singapore and Vietnam. It highlights the importance of the policy context, especially the commitment of the government in allocating the necessary resources and the support of the implementers, as well as the public bureaucracy's effectiveness, as the critical factors responsible for effective policy implementation. The comparative analysis shows that the public bureaucracies in Singapore and Malaysia are more effective in policy implementation than their counterparts in Indonesia, the Philippines and Vietnam because of their favourable policy contexts and higher level of organizational effectiveness. The focus on policy context and the public bureaucracy's role in the policy-making process and its implementation of two ASEAN policies will be of interest to policymakers, civil servants, scholars and students concerned with enhancing policy implementation in the ASEAN countries"-- Provided by publisher.